2018
DOI: 10.1542/peds.2017-3091
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Impairment Among Extremely Preterm Infants in the Neonatal Research Network

Abstract: Extremely preterm children are at risk for NDI. Over time, the rate of moderate to severe NDI did not differ, but the rates of severe CP decreased, and mild CP increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(137 citation statements)
references
References 36 publications
2
127
2
6
Order By: Relevance
“…For the factors that correlated with the TBV/HC, we further investigated the risk for the overestimation of TBV, which was defined by a zTBV measured of 1.5 or smaller than the zTBV predicted . 22 Sensitivity and specificity were used for the evaluation. For the continuous variables (eg, BBW, gestational age at birth, or mCI), the maximum value of the Youden's index on the receiver operating characteristic (ROC) curve 23 was used to define the cutoff value for calculating the sensitivity and specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the factors that correlated with the TBV/HC, we further investigated the risk for the overestimation of TBV, which was defined by a zTBV measured of 1.5 or smaller than the zTBV predicted . 22 Sensitivity and specificity were used for the evaluation. For the continuous variables (eg, BBW, gestational age at birth, or mCI), the maximum value of the Youden's index on the receiver operating characteristic (ROC) curve 23 was used to define the cutoff value for calculating the sensitivity and specificity.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effects of neurodevelopmental risk factors on the HC‐TBV relationship, the correlation between 14 factors, listed in Table , and the TBV/HC ratio were evaluated using Spearman's rank moment correlation coefficient. For the factors that correlated with the TBV/HC, we further investigated the risk for the overestimation of TBV, which was defined by a zTBV measured of 1.5 or smaller than the zTBV predicted . Sensitivity and specificity were used for the evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The EPICURE cohort study from England reported that rates of CP and severe disabilities among surviving children were unchanged between 1995 and 2006 [21]. The US National Institute of Child Health and Human Development Neonatal Research Network reported a decrease in the prevalence of severe CP among extremely preterm infants in the period 2011–2014 [22], and a recent population-based cohort study from Australia documented an increase in non-CP motor impairment among extremely preterm infants from 1991–2005, while rates of CP remained relatively constant [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Extremely preterm birth carries a high risk of death or long-term cerebral impairment. With a current mortality of about 25% and a prevalence of psychomotor impairment in approximately 20% of survivors, more than 10,000 will die each year and a further 10,000 will suffer from cerebral palsy and/or moderate-tosevere cognitive impairment (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%